THE IMPACT OF DIGITAL IMMERSION ON ENGLISH LANGUAGE ACQUISITION: A SHIFT FROM TRADITIONAL PEDAGOGY - Mahmudova Mehrinigor Azamat qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This study investigates the profound influence of digital immersion on English as a Second Language (ESL) acquisition in the contemporary era. While traditional classroom methodologies prioritize structural grammar and rote memorization, digital environments foster pragmatic fluency and authentic communication. Using a mixed-methods approach, this research analyzes how exposure to social media, streaming platforms, and AI-driven tools affects learners’ proficiency. The findings suggest that while digital immersion significantly accelerates vocabulary breadth and listening comprehension, it presents unique challenges for formal academic writing and grammatical precision.